Digital Education and citizenship training in High School: perspectives from BNCC - Abdon, Jorge (2025)
This work analyzes the perspectives of digital education and training for citizenship based on the National Common Curricular Base-BNCC. Considering the current educational context, this article aims to contribute to strengthening dialogue and the participation of individuals in civic education through technological knowledge, contributing to choices aligned with their life project. This work is the result of bibliographic and documentary research, with the BNCC as the main document analyzed. It is concluded that the digital education proposal present in the BNCC can contribute to the construction of life projects and education for citizenship among students of high school. However, it still requires structural investment to provide conditions for the implementation of digital education.